Exocyclic self-assembly behavior of carboxylic acid and lariat ether macrocyclic hosts: regulation by pendent arm1. Issue 84 (16th September 2015) - Guo, Rong; Wang, Wei; Yang, Weiping; Chen, Yuanyin; Gong, Shuling
<x xml:space="preserve">Abstract</x> An exocyclic supramolecular building block through O–H⋯N hydrogen bonding interaction for the assembly of di-sidearm dibenzo-diazacrown ethers bearing a flexibility sidearm with PTA acid.